Snail intermediate host occurrence recorded by citizen scientists in rural Uganda and the Democratic Republic of the Congo - Noelia Valderrama-Bhraunxs; Larissa Bonifacio; Julius Tumusiime; Germain Kapour; Daisy Namirembe; Casim Umba-Tolo; Grace Kagoro-Rugunda; Patrick Mitashi-Mulopo; Joule Mandinga; Liesbet Jacobs; Tine Huyse (GigaByte)
Snail-borne parasitic diseases, such as schistosomiasis and fascioliasis, pose significant public health and economic challenges worldwide. Schistosomiasis affects over 250 million people globally, with most cases in sub-Saharan Africa, while fascioliasis contributes substantially to livestock morbidity and economic losses. Freshwater snails (Biomphalaria, Bulinus, and Radix spp.) act as intermediate hosts, making their surveillance critical for disease control. Mass drug administration alone is insufficient, as high reinfection rates highlight the need for complementary strategies, including targeted snail control. To address limited malacological capacity and logistical constraints, the ATRAP project trained 50 citizen scientists in Uganda and the Democratic Republic of the Congo to monitor intermediate host snails at the genus level. Between 2020 and 2023, citizens recorded 31,490 snail occurrences. Data quality was ensured through automatic validation and manual verification of submitted snail pictures. This rigorously curated dataset, combining citizen science with expert validation, provides valuable insights for mapping snail distributions, identifying high-risk transmission areas, and developing sustainable, cost-effective snail control strategies.